2018
DOI: 10.22545/2018/00105
|View full text |Cite
|
Sign up to set email alerts
|

Digital Humanities and Transdisciplinary Practice: Towards a Rigorous Conversation

Abstract: he digital humanities is frequently and casually associated with supradisciplinarity; either as multidisciplinarity, interdisciplinarity or transdisciplinarity. This paper endeavors to put digital humanities into a more rigorous and critical conversation with the three forms. Two broad approaches to distinguishing the three supradisciplinary forms are represented, namely, the definitional and theoretical approaches; with the latter emphasized as providing more analytical traction for a critical conversation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Understanding global issues, such as climate issues, ecosystems, pandemics, or migrations, involves the need to understand complex systems. Complex systems have distinct properties such as nonlinearity, emergence, spontaneous order, adaptation, and feedback loops, amongst others [41]. A key aspect of the challenges involved in developing knowledge about planetary wellbeing is what we need to promote the adoption of new scientific developments, such as network science [42], big data, or data science approaches.…”
Section: Knowledge Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding global issues, such as climate issues, ecosystems, pandemics, or migrations, involves the need to understand complex systems. Complex systems have distinct properties such as nonlinearity, emergence, spontaneous order, adaptation, and feedback loops, amongst others [41]. A key aspect of the challenges involved in developing knowledge about planetary wellbeing is what we need to promote the adoption of new scientific developments, such as network science [42], big data, or data science approaches.…”
Section: Knowledge Challengesmentioning
confidence: 99%
“…Another important consequence of the global and complex nature of planetary wellbeing is the need for the different disciplines working to work together in modes that are multidisciplinary (drawing on knowledge from different disciplines but remaining within the boundaries of those fields), interdisciplinary (analyzing, synthesizing, and harmonizing links between disciplines into a coordinated and coherent whole) and transdisciplinary (using a shared conceptual framework drawing together new disciplinary-specific theories, concepts, and approaches to address common problems) [41]. The assumption here is that the global challenges we face are so complex that their thorough examination and solution requires different scientific disciplines to work in alliance with each other [43][44][45].…”
Section: Knowledge Challengesmentioning
confidence: 99%
“…This will strengthen their capacity to work alongside colleagues from other disciplines throughout their careers. The adoption of a multi-, inter-, and trans-disciplinary approach ( 16 ) has several implications, such as the need of a faculty with a diverse background in the disciplines involved in the corpus of Planetary Health. In the current stage of the MSc in Planetary Health, the diversity of disciplinary backgrounds is well-stablished in the team of course instructors, in the academic committee that supervised the design of the programme and the modules, and in the external advisory committee who played a key role during the accreditation phase.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence of new methodologies and approaches to include Planetary Health in health curricula ( 13 15 ). Among the different types of curricula, postgraduate education has received little attention and yet it offers a unique opportunity to train already qualified professionals from different disciplines to work multi- (drawing on knowledge from different disciplines but remaining within the boundaries of those fields), inter- (analyzing, synthesizing, and harmonizing links between disciplines into a coordinated and coherent whole), and trans-disciplinary (using a shared conceptual framework drawing together new disciplinary-specific theories, concepts, and approaches to address common problems) ( 16 ). In the GCCHE study cited above, only one institution reported having a master's or certificate programme in climate and health.…”
Section: Introductionmentioning
confidence: 99%
“…Open Sci. 10: 230574 analyses 6 ; otherwise, they were performed by the authors. The cadences are indicated and will be referred to in the discussion of the results as an indicator of harmonic stability.…”
Section: Datasetmentioning
confidence: 99%